Metal oxide nanofillers induced changes in material properties and related applications of polymer composites - Al-Gunaid, Murad Qassim Abdulraqeb; Maheshwarappa, Gayitri Hebbur; Shivanna, Shashikala Badaga; Dhaif-Allah, Mohammed Ali Hussein; Ahmed, Waled Abdo; Al-Ostoot, Fares Hezam (European Journal of Chemistry, 2023)
Nanometal oxides have attracted considerable research interest because of the widespread applications in which nanomaterials can be synthesised in various oxide forms that can adopt various structural geometries with unique electronic band structures. Additionally, nanometal oxides provide unique features imputed to quantum confinement effects that stimulate changes in their optical, electrical, and optoelectronic behaviours. Meanwhile, introducing such nanometal oxides into host polymeric materials enables the formation of advanced polymeric nanocomposites with versatile properties. Even so, the utilisation of such nanocomposites in diverse potential applications requires a fundamental understanding of their inherent material functionalities. Therefore, this document aims to demonstrate the importance of polymer nanocomposites with a special focus on the impact of nanometal oxides to enhance the optical and electrical behaviours of polymer composites for advanced optoelectronic and energy storage applications.